Submission of bank guarantee for advance payment not yet recovered on contract for construction of BRAC University new campus project - Brac University (Brac University, 2023)
This record consists of general correspondence regarding submission of bank guarantee for advance payment not yet recovered on contract for construction of BRAC University new campus project.